Definição de uma política de compras em uma farmácia utilizando ferramentas de gestão de estoques - Silva, Vitória Lorena Ferreira da (Universidade Federal Rural do Semi-Árido, 2019)
Since inventory management is critical to the survival of a company, it is necessary to define the rules that will guide the purchasing decisions and the inventory management of the company. The Pharmacy object of this study, was in financial imbalance caused by debts with suppliers, due to the lack of a formal management of the acquisition of medicines. This study aimed to propose a purchasing policy in a pharmacy located in the city of Mossoró-RN, using the tools of inventory management: ABC-XYZ Analysis, Economic Purchase Lot and Continuous and periodic review systems. The results indicate that the periodic review policy presents the greatest cost reduction, precisely 21.91% in relation to the real situation, and according to the data discussed, it is able to supply the demand as well as the policy of continuous replenishment , showing better performance and, therefore, is the most appropriate purchasing policy to be adopted by the drugstore.
Monografia
Keywords: Gestão de estoques; Reposição contínua; Reposição periódica; Análise ABC-XYZ; Inventory management; Continuous replacement; Periodic replacement; ABC-XYZ analysis; ENGENHARIAS::ENGENHARIA DE PRODUCAO